Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 5 - Polynomials and Factoring - 5.7 Solving Quadratic Equations by Factoring - 5.7 Exercise Set - Page 352: 38


$x=\left\{ 1 \right\}$

Work Step by Step

Factoring the given equation, $ x^2+1=2x ,$ results to \begin{array}{l}\require{cancel} x^2-2x+1=0 \\\\ (x-1)^2=0 \\\\ (x-1)(x-1)=0 .\end{array} Equating each factor to zero (Zero Product Principle), then the solutions to the equation, $ (x-1)(x-1)=0 ,$ are \begin{array}{l}\require{cancel} x-1=0 \\\\ x=1 ,\\\\\text{OR}\\\\ x-1=0 \\\\ x=1 .\end{array} Hence, $ x=\left\{ 1 \right\} .$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.